Risk Factors and Effectiveness of Implementing Multi-Construction Projects for Development of Industrial Facility Sector in Indonesia - Siahaan, Saut B; Alisjahbana, Sofia W.; Gondokusumo, Onnyxiforus (IJEBD (International Journal of Entrepreneurship and Business Development), 2024)
Purpose: Multi-project management of industrial facility construction has high challenges and complexity. Various factors influence the effectiveness and risks of multi-project implementation. A separate management method is required in implementing multi-projects compared to single projects. An organization must manage multiple projects using organizational resources and personnel. This research aims to obtain best practices in managing multi-project construction of industrial facilities in Indonesia and understand the cause and effect and influence between variables. Design/ methodology/ approach: This research uses a qualitative approach based on literature observations, reviews, and surveys of the construction sector of industrial facilities in Indonesia. Survey data were analyzed by looking for essential themes related to the research questions. The survey results show that six factors and 50 important variables influence the implementation of multi-project industrial facility construction. These factors are human resources, organization, environment, construction, external, design & technical, and business. Findings: This research provides an overview of the practices and challenges of multi-project management of industrial facility construction in Indonesia. This research also provides recommendations for developing dynamic system models that can assist in managing the risks and impacts of multi-project implementation. Paper type: Research paper